PENINGKATKAN MANAJEMEN PESERTA DIDIK BERBASIS SEKOLAH MELALUI SUPERVISI MANAJERIAL DI SMPN 1 SUNGAI RAYA - Riyadi, Slamet (Universitas Tanjungpura, 2020)
AbstractThe principal has a great duty and responsibility in encouraging and facilitating the quality of educational program at a school. One of this is carrying out the main managerial duty and supervisory on teachers and education staff. According to the results of managerial supervision that have been carried on from January to April 2018, it was obtained 56% of all components of students management. To overcome this matter, the researcher has conducted a School Action Research entitled The Principal’s Effort In Improving Students Management Of School-Based Through Managerial Supervision of Smp Negeri 1 Sungai Raya. This research was conducted by involving the vice principal of students affairs and administration staff. The target of this research is the achievement of vice principal of students affairs and administration staff in the students management of school-based. The students management of school-based is a regulation for students that is began when they registered as the student until they have graduated at the school. This research was conducted through two cycles, in the first cycle 75% was obtained with good qualifications and 4 incomplete components of 25% with medium qualifications. In the second one, all components of the management of students have completed (100%). Based on these results, the principal has more motivation to improve the achievement of other school employees in order that completion of school administrative duties run better.Keywords: Principal, Student Management, Managerial Supervision